2009
DOI: 10.2478/v10144-009-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neural Network Technologies for Price Forecasting in the Liberalized Electricity Market

Abstract: Application of Neural Network Technologies for Price Forecasting in the Liberalized Electricity MarketThe paper presents the results of experimental studies concerning calculation of electricity prices in different price zones in Russia and Europe. The calculations are based on the intelligent software "ANAPRO" that implements the approaches based on the modern methods of data analysis and artificial intelligence technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is to be noted that the SA algorithm can select a neural network model for which the input parameters will be the most significant. Experimental computations [15] have indicated a rather high accuracy forecasting based on intelligent neural approach in comparison with the regression models, and with traditional neural network forecasting. But these calculations have shown that intelligent model is not very good "at guessing" the peak zones.…”
Section: A Artificial Neural Network Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that the SA algorithm can select a neural network model for which the input parameters will be the most significant. Experimental computations [15] have indicated a rather high accuracy forecasting based on intelligent neural approach in comparison with the regression models, and with traditional neural network forecasting. But these calculations have shown that intelligent model is not very good "at guessing" the peak zones.…”
Section: A Artificial Neural Network Modelsmentioning
confidence: 99%
“…The short-term EPF In the paper [15], [28] an intelligent approach based on the neural network technologies to EPF for different lead time intervals has been proposed. This approach has demonstrated good results in comparison with traditional neural network forecasting [6].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The short-term forecasting of power system parameters can be carried out both with the aid of classical approaches of dynamic estimation, statistical methods of analysis of time series and regressive models, and with the aid of artificial intelligence. Many techniques have been employed for such purposes, including machine learning techniques -artificial neural networks (ANNs) [12,10], support vector machines (SVMs) [8], random forest models [8,22] and etc. Moreover, time series models, like ARIMA, GARCH models [13,11], Kalman filter-based algorithm [9,30] have also been proven to be effective in the power system parameters forecasting.…”
Section: Introductionmentioning
confidence: 99%